Essentials of maternity, newborn, and women's health nursing - Ricci, Susan Scott (2017)
"Since the health care focus of women and their families has expanded well beyond our nation's borders, more cultural and global aspects of maternity and women's health care have been added to this fourth edition. The United States is part of the international community, and as such nurses must understand and respect diverse cultures and their customs to truly play an important role as a global partner. Nurses care for a variety of women from many continents, thus they have to be armed with appropriate tools to meet their client's diverse needs. Also more evidence-based research findings have been included in this fourth edition for nurses to validate their practice and interventions"--
Keywords: Maternity nursing; Gynecologic nursing; Maternal-Child Nursing; Obstetric Nursing; Pregnancy Complications -- nursing